Polygonum oktaysinanoglui sp. nov. (Polygonaceae) from Türkiye and Multi-Access Key to Turkish Polygonum - Keski̇n Mustafa (Phytotaxa, 2025)
Polygonum oktaysinanoglui, a new species from Hatay (Türkiye), is described based on some morphological traits. This species is similar to P. salebrosum (endemic to Türkiye) from which differs in having shorter woody stocks, tepal 2.7–5 mm (vs. 2.3–3.1 mm in P. salebrosum), fruits 5 mm (vs. at most c.4 mm), and leaves petiolated (vs. sessile to subsessile), leafy and loose inflorescences (vs. leafless and almost congested inflorescences), and nuts 5 mm at most equal to tepal (vs. at most 3.5 mm and exserted to tepal). A letter key system was developed to identify the Polygonum species in Türkiye due to the difficulties to naming Polygonum taxa correctly.